1040. Comparative Characteristics of Patients With Pseudomonas Bacteremia Receiving Intravenous Only vs. Intravenous Followed by Oral Therapy. (26th November 2018) - Vu, Trung; Yang, Linda; Hopkins, Teri; Frei, Christopher R; Cadena, Jose; Walter, Elizabeth
Abstract: Background: There have been few studies on treatment approaches to Pseudomonas bacteremia and transition from intravenous (IV) to oral (PO) therapy. The objective of this study was to determine whether IV to PO switch therapy was associated with worse 30-day mortality than IV only therapy for patients with Pseudomonas bacteremia. Methods: This was a retrospective cohort study comparing patients with ciprofloxacin-susceptible Pseudomonas bacteremia treated with IV only to those transitioned from IV to PO switch therapy. We evaluated 153 consecutive patients from January 2008 to October 2017; of those, 119 (78%) had ciprofloxacin-susceptible Pseudomonas . We excluded 68 patients due to polymicrobial bacteremia, <3 days, or >21 days of therapy. This left 54 patients for evaluation, 29 of whom received IV only, and 25 with IV to PO switch therapy. Results: Median patient age was 66 years for both groups. IV only therapy was associated with Hispanic ethnicity (48% vs. 28%, P = 0.0271, hospital-acquired infection (52% vs. 13%, P = 0.0035), Pitt bacteremia score (median [interquartile range] of 3 [2–3] vs. 1 [0–2], P = 0.0007), duration of IV therapy (median [interquartile range] of 11 [7–14] vs. 4 [2–6], P < 0.0001), and 30-day mortality (31% vs. 0%, P = 0.0023). The IV only group was more likely to have an associated diagnosis of pneumonia (44% vs. 16%, P = 0.0264) and less likely to have an associated diagnosis of urinary tract infection (17% vs. 60%, P = 0.0021). In a multivariate analysis, with IV only vs. IV to PO switch therapy as the independent variable, mortality as the dependent variable, and pneumonia and UTI as covariates, IV only was independently associated with mortality ( P = 0.0006). Conclusion: Patients on IV only therapy were more likely to die at 30 days than those on IV to PO switch therapy, when accounting for differences in diagnosis of pneumonia and UTI, suggesting clinician recognition of increased severity of illness in the IV only group. Disclosures: All authors: No reported disclosures.